Contemporary conditions of recreational activity - Zdebski, Janusz (Health Promotion & Physical Activity, 2018)
Active human recreational behaviour is a result of both internal, subjective as well as external, situational factors. The need of emotional stimulation is a significant factor determining the form of recreational activity. It induces a man to engage in risky behaviour to have new, strong emotional experience. This need is best explained by Zuckerman’s concept. The search for experiences is biologically conditioned. Promoting fashion for recreational activity in the society is the result of perceiving its positive impact on human health. On the other hand, the progressing commercialization of all spheres of social life has contributed to the promotion of recreational activity as a product for sale. For people, recreational activity is an embodiment of free choice and allows for full creation, which corresponds to the fact that in post-industrial societies it displaces work from the centre of social systems. The best effects for a man are brought by recreational activity carried out as an expression of the internal needs of the individual.